Two-Level Model of Attitudes and Beliefs Influencing Higher Order Thinking (HOT) Skills in Mathematics - Elizar,Elizar (2021)
Abstract This article focuses on a two-level model analysis of attitudes and beliefs affecting students’ higher order thinking (HOT) skills in mathematics in Aceh, Indonesia. The data used are nested within the hierarchical ordering of both student (level 1) and teacher (level 2). The variables used at level 1 in the study include liking mathematics, valuing mathematics, confidence in mathematics, and individual judgement of mathematics ability, as well as beliefs concerning mathematics related to lower order thinking (LOT) and higher order thinking (HOT). The variables at level 2 involve beliefs concerning mathematics teaching related to LOT and beliefs concerning mathematics teaching related to HOT. The analysis reveals that there are four variables at level 1 contributing to student HOT skills in mathematics: liking mathematics, individual judgement of mathematics ability, beliefs concerning mathematics related to LOT, and beliefs concerning mathematics related to HOT. At level 2, the one variable affecting student HOT skills in mathematics is teacher beliefs concerning mathematics related to HOT.